A geografia do turismo do Estado do Rio de Janeiro: conservatória um estudo de caso - Aranha, Raphael de Carvalho (2014)
This master paper aims to perform a study in the urban area of the Conversatória County located in the Valença district, Rio de Janeiro State in order to analyze the cultural tourism that occurs on site. It was sought to understand the several variables in order to assess the role of the music style named as serestas, which is performed in the serenades and solaratas every weekend as a way to attract tourists and locals. In order to achieve this goal, 105 questionnaires were administered to tourists and locals at different age groups. Such questionnaires revealed that, regardless of age, most people are attracted to the village because of the quietness, hospitality and climate of the place, although the seresta music style also plays an important role while attracting tourists and locals. In addition, the current paper introduced the official regionalization of the Rio de Janeiro State tourism, promoted by the Tourism Ministry in 2005, describing its main touristic regions (Metropolitan area, Costa Verde, Serra Verde Imperial, Agulhas Negras, Costa do Sol and Vale do Café) from the physical, demographical and localization characteristics, deepening the studies when an analysis of the Vale do Café touristic region, in the Vale do Paraíba Fluminense was carried out, an area where the coffee production prevailed during the XIX century as the birthplace of such cultural manifestation and legacy for the locals cultural identity, becoming the greatest symbol of the Conversatória village